Estimation of Prolactin and Some Biochemical Parameters in Some Psychotic Male Patients Treated with Risperidone in Tikrit City - Kader, Marwa Abdulsalam (Journal for Research in Applied Sciences and Biotechnology, 2023)
The primary purpose of this research is to examine the impact of taking risperidone by psychotic individuals on serum levels of prolactin hormone as well as a few biochemical indicators (total protein and liver enzymes AST and ALT). The experiment required collecting fifty blood samples and dividing them into two groups: the first group consisted of normal, healthy persons who served as a control. In contrast, the second group consisted of psychotic patients treated with risperidone at a dosage of two milligrams per day. The findings of this study showed that There were significant increases in total protein content at levels (P≤ 0.05) of the group 2 compared to control, and there were significant gains in liver enzymes (AST and ALT) concentration range at levels (P ≤0.05) of the second group in comparison to the control group, and there were substantial improvements increases in prolactin hormone concentrations at levels (P≤ 0.05) of the second group in compared to control.